2008
DOI: 10.1091/mbc.e07-09-0858
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosome-deficient Cells Lose Cytochromecthrough Proteasomal Degradation but Survive by Autophagy-dependent Glycolysis

Abstract: Cytochrome c release from mitochondria promotes apoptosome formation and caspase activation. The question as to whether mitochondrial permeabilization kills cells via a caspase-independent pathway when caspase activation is prevented is still open. Here we report that proneural cells of embryonic origin, when induced to die but rescued by apoptosome inactivation are deprived of cytosolic cytochrome c through proteasomal degradation. We also show that, in this context, those cells keep generating ATP by glycoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 50 publications
(68 reference statements)
2
42
0
Order By: Relevance
“…However, in order to assess the PONR, a combination of recommended detection methods 1,5,10,14 is suggested. Further it which control characteristic 39 and often progressively developing 40 morphological changes. Control of the PONR position through the cell's metabolic efforts would ensure the highest likelihood of cellular preservation.…”
Section: Dynamics Within Modes Of Cell Deathmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in order to assess the PONR, a combination of recommended detection methods 1,5,10,14 is suggested. Further it which control characteristic 39 and often progressively developing 40 morphological changes. Control of the PONR position through the cell's metabolic efforts would ensure the highest likelihood of cellular preservation.…”
Section: Dynamics Within Modes Of Cell Deathmentioning
confidence: 97%
“…The cell protects itself from dying, therefore is suggested that kinetic parameters for autophagy, apoptosis and necrosis as well as cell specific parameters, intra-and extracellular metabolic parameters and insult parameters be carefully considered (Table 1). For example, a combination of data on basal autophagic flux, 10,23,41 the time needed to reach its maximal attainable activity, as well as vital dye uptake dynamics [42][43][44] and onset of dissipation of mitochondrial transmembrane potential ∆Ψ m 33 should be placed into context with the cell's metabolic substrate preference and ATP household over time 39 in order to describe the PONR. It is crucial that multiple parameters be acquired at multiple points in time, and examined in context with one another, to capture the dynamic character of temporal signalling during cellular response.…”
Section: Autophagy and The Dynamics Between Modes Of Cell Deathmentioning
confidence: 99%
“…48 By targeting glycogen, lipids and proteins to lysosomes, autophagy guides the breakdown of these macromolecules, thereby producing metabolic precursors that can sustain oxidative phosphorylation and glycolysis. 49,50 In cancer cells from solid undernourished tumors, response to radiotherapy or DNA-damaging chemotherapy triggers ATP production by autophagy, which may have an essential role in DNA repair ( Figure 1, box ii). Supporting this hypothesis, the inhibition of autophagy suppressed ATP generation and increased mitotic catastrophe in glioma cells treated with temozolomide (TMZ).…”
Section: The Role Of Autophagy In Dna Repairmentioning
confidence: 99%
“…Some studies conclude that autophagy could be a protective procedure for cells and tissues to sustain hypoxia/ ischemia. 26,27) On the other hand, there are also a number of papers documenting a deleterious role for autophagy. 17,28) A reliable explanation for these phenomena is that autophagy is primarily a protective process to maintain homeostasis under the stress of cerebral ischemia/reperfusion.…”
Section: )mentioning
confidence: 99%